Pemodelan Dispersi CO dan NO2 pada Industri Pengadaan Uap Panas (STEAM) di Kabupaten Karawang - Fauzan, Rizq Siraj; Adzillah, Wilma Nurrul; Fauzie, Azis Kemal (Universitas Tanjungpura, 2025)
Air pollution caused by industrial activities has become a critical issue due to its significant impact on public health and the environment. This study aims to model the dispersion of air pollutants in the form of carbon monoxide (CO) and nitrogen dioxide (NOâ‚‚) emitted from a biomass boiler stack at a steam supply industry located in Karawang Regency. The modeling was conducted using the AERMOD software, integrated with AERMET for meteorological data processing and AERMAP for topographical data input. Emission data were obtained from direct monitoring of industrial sources, while meteorological data were sourced from the Climate Data Store. The modeling was carried out for two seasonal periods, namely the dry season and the rainy season, to evaluate the influence of meteorological variables on pollutant distribution. The air quality modeling results indicated that the highest concentrations occurred during the dry season, with 1-hour and 8-hour CO concentrations of 22.46 Î¼g/m ³ and 8.52 Î¼g/m ³, respectively, and 1-hour and 24-hour NOâ‚‚ concentrations of 76.75 Î¼g/m ³ and 22.71 Î¼g/m ³, respectively. All concentrations remained below the established ambient air quality standards. The conclusion of this study indicates that seasonal meteorological conditions influence pollutant dispersion, with higher concentrations observed during the dry season compared to the rainy season; however, the levels remained within regulatory safety limits.